Contact-free conductivity probing of metal nanowire films using THz reflection spectroscopy. (14th March 2019) - Layani-Tzadka, Muriel E; Krotkov, Daniel; Tirosh, Einat; Markovich, Gil; Fleischer, Sharly
Abstract: We utilize time-domain Terahertz (THz) reflectivity measurements for characterizing the surface conductivity of Polyethylene-terephthalate coated with nanowire (NW) films to form novel transparent electrodes (TE). We find good correspondence between the film conductivity and the THz-field reflectivity that provide uniquely desirable means for non-destructive, contactless conductivity measurements of large area NW-based-TEs. We demonstrate the robustness of THz reflectivity measurements to deviations invoked on NW film composition and film uniformity. The dependence of THz reflectivity on area NW coverage follows an anisotropic effective medium model for the dielectric constant.